2010
DOI: 10.3109/03008200903280115
|View full text |Cite
|
Sign up to set email alerts
|

Birefringence of the Secretory-Stage Enamel Organic Extracellular Matrix from Rats Submitted to Successive Injections of Bisphosphonates

Abstract: The aim of the present study was to assess birefringence of the secretory-stage enamel organic extracellular matrix (ECM) and mechanical properties of mature enamel from rats treated with bisphosphonates. Longitudinal sections were obtained from upper incisors of rats that had been submitted to injections of bisodic etidronate (8 mg/Kg/day), sodium alendronate (30 microg/Kg/day), or sodium chloride as control (8 mg/Kg/day) for 42 days. Sections were immersed in 80% glycerin for 30 min and optical retardation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
(55 reference statements)
0
6
0
2
Order By: Relevance
“…Birefringence is the anisotropy caused by the difference between the two refractive indices of a substance, and it occurs as a consequence of ordered polymerization of macromolecules, such as organic matrix of enamel and collagen fibers in the periodontium 22,23 . One of the key functional characteristics of the acellular cementum is the insertion of collagen fibers from the PDL, the so‐called Sharpey fibers 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Birefringence is the anisotropy caused by the difference between the two refractive indices of a substance, and it occurs as a consequence of ordered polymerization of macromolecules, such as organic matrix of enamel and collagen fibers in the periodontium 22,23 . One of the key functional characteristics of the acellular cementum is the insertion of collagen fibers from the PDL, the so‐called Sharpey fibers 23 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the effects of etidronate (HEBP), a nonaminobisphosphonate, on collagen fibrillogenesis, matrix synthesis, and mineralization of dentin have been reported (Beertsen et al,1985; Larsson,1974; Ogawa et al,1989; Sakai et al,1999; Takano et al,1998). HEBP has also been shown to affect enamel mineralization (Espírito Santo et al,2010; Fouda et al,1989, 1991, 1992; Weile et al,1990, 1993), ameloblast morphology (Fejerskov et al,1990; Josephsen et al,1990), and ameloblast functions, including effects on protein synthesis and secretion (Fuangtharnthip et al,2000; Yamada et al,2000), with development of hypoplasia and formation of subameloblastic cysts (Fejerskov et al,1990; Fouda et al,1989, 1991, 1992; Simmelink,1987). …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the DXA analysis revealed an increase in the bone mineral density of the proximal tibial metaphysis after exposure to sodium alendronate, which confirms previous reports (Freundlich and Alon,2008; Inoue et al,2008; Kawate et al,2010). Despite being widely used, few studies evaluated the effect of sodium alendronate in dental hard tissue formation in vivo, and those available are limited to enamel (Espírito Santo et al,2010; Massa et al,2006). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations